2013
DOI: 10.1071/fp12179
|View full text |Cite
|
Sign up to set email alerts
|

Drought adversely affects tuber development and nutritional quality of the staple crop cassava (Manihot esculenta Crantz)

Abstract: Summary 16Cassava is a staple for over 850 million people, but it is toxic unless properly processed. A 17 monotonous cassava diet often coincides with outbreaks of diseases such as konzo, especially on cassava as it is drought tolerant, but it may also be due to an increase in cyanogenic 31 glucosides. Episodic droughts are forecast to become more common in many cassava-32 growing regions. We therefore sought to quantify the effect of water-stress on both yield and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 29 publications
5
67
0
Order By: Relevance
“…However, health of people may be affected [31], particularly in years when drought has affected other crops, which increases people's dependency in cassava. In addition to higher consumption of cassava roots, drought generally increases CG levels in them [32].…”
Section: Nutritional Value Of Cassava Rootsmentioning
confidence: 99%
“…However, health of people may be affected [31], particularly in years when drought has affected other crops, which increases people's dependency in cassava. In addition to higher consumption of cassava roots, drought generally increases CG levels in them [32].…”
Section: Nutritional Value Of Cassava Rootsmentioning
confidence: 99%
“…The papers by Gray et al (2013) and Vandergeer et al (2013) in this volume emphasise the below ground processes and acquisition side of the equation, which are still considerably less explored than above ground plant functions. Plants appear to be able to capitalise on higher atmospheric CO 2 so long as they have access to adequate N, underlining the importance of nitrogen use efficiency in crops (Reich and Hobbie 2012).…”
mentioning
confidence: 99%
“…Moreover, the increased severity and duration of heat waves, coupled with higher evapotranspiration, are likely to decrease soil moisture. In a study relevant to these probable scenarios, Dias de Oliveira et al (2013) Vandergeer et al (2013) showed that cassava yields and quality are sensitive to drought.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of CG is dependent on cultivar, growth conditions, farming practices and age of plant (Butler et al, 1973;McMahon et al, 1995). Vandegeer et al (2013) reported that water deficit resulted in a 3 to 4 folds increase of CG concentration in young leaves and tubers respectively. Butler et al (1973) concluded that altering farming practices to reduce cyanide levels was not practical as most cassava farming systems do not possess irrigation or machinery, further suggesting that selective breeding for cultivars with reduced production of cyanide compounds was more feasible.…”
Section: Cyanide Productionmentioning
confidence: 99%